Peran Kinerja Lingkungan pada Pengaruh Gender Diversity terhadap Kinerja Keuangan - Rina Yuniarti; Ahmad Sumarlan; Ahmad Junaidi; Pedi Riswandi (UNIVED Press, 2023)
The purpose of this study was to determine the effect of gender diversity on financial performance with a mediating environmental performance. This population is manufacturing companies listed on the Indonesia Stock Exchange (BEI) for 2017-2019. The sample in this study amounted to 249 companies with sampling technique used purposive sampling. The data analysis technique is path analysis processed using WarpPLS 6.0. the results of gender diversity have an effect on financial performance and environmental performance does not mediate the effect of gender diversity on financial performance and not mediate the effect of gender diversity on financial performance